Pengembangan Media Pembelajaran Berbasis Tailwind CSS dan GeoGebra Pada Materi Geometri Transformasi Untuk Kelas IX MTsN 2 Mataram - Hidayah, Khulaeni Hidayatul; Amrullah, Amrullah; Kurniawan, Eka (Griya Journal of Mathematics Education and Application, 2025)
This research aims to develop a learning media based on Tailwind CSS and GeoGebra in the topic of Transformation Geometry for ninth-grade students at MTsN 2 Mataram. The background of this study is students’ difficulties in understanding transformation geometry concepts due to their abstract nature and the limitations of conventional learning media, which tend to be less interactive. The method used in this study was Research and Development (R&D) with ADDIE (Analysis, Design, Development, Implementation, Evaluation) as the development model. The research sample consisted of ninth-grade E class students of MTsN 2 Mataram. The developed learning media was evaluated for its feasibility by media experts and tested with students. The validation results showed that the developed learning media met the feasible criteria with a feasibility percentage of 74,6%. The practicality test through student questionnaires also indicated a very practical category with a practicality percentage of 93,65%. Therefore, the learning media based on Tailwind CSS and GeoGebra is considered feasible and practical to be used as a learning aid in teaching transformation geometry at schools.